Preliminary approach to the study of the ‘Tappatino’ area of Suasa - Francesca Bindelli (Groma, 2024)
This paper presents a reconstruction study of the ‘Tappatino’, a rustic farmhouse in the Archaeological Park of the Roman city of Suasa (Castelleone di Suasa, AN). As a multi-stratified site, a wide range of data from both archive sources and archaeological research has been analysed as a starting point for this study. In addition, topographic surveys and the stratigraphic analysis of the masonry were conducted. Finally, the paper describes the application of the Extended Matrix Framework (EMF) to the 3D reconstruction of this area and suggests a reconstructive proposal for the Roman imperial age.